0488 Clinical Applications of a Modified Home Sleep Apnea Test in the Diagnosis of Obstructive Sleep Apnea. (27th April 2018) - Robinson, K; Sultan Ali, I; Laws, R
Abstract: Introduction: Obstructive Sleep Apnea (OSA) affects up to 17% of civilian adults and 87% of older male Veterans. The disorder is associated with higher risk of mortality and reduced quality of life in addition to a staggering estimated economic cost of 65-165 billion annually. An important diagnostic modality is home sleep apnea testing (HSAT), a modified version of HSAT was evaluated by the Memphis VA sleep clinic for its ability to provide reliable results, reduce cost, and expand access. Methods: A retrospective chart review of all patients who underwent a modified HSAT from January 1, 2011-December 31, 2016 were included in the sample. The diagnostic results of modified HSAT, clinical access and cost savings were analyzed. Results: The sample consisted of 961 Veterans, the majority were male (89.6%) and of minority ethnicity (55%), average age was 50, BMI of 37, and AHI of 28.9. The modified HSAT diagnosed 38% of the sample with severe OSA, 24% with moderate OSA, and 21% with mild OSA. The remaining 16% of patients had indeterminate results, of that subset who completed a follow-up PSG, 50% were diagnosed OSA. Overall, the modified HSAT confirmed the clinical suspicion of OSA 84% of the time with one single night study. The modified HSAT was found to have 97.1% sensitivity and 100% specificity confirming the clinical probability of OSA. The modified HSAT is also cost effective with estimated savings over the study period of over 1 million dollars when compared to Medicare reimbursement rates. Lastly, by adding the modified HSAT the SHC increased assess by 37.5%. Conclusion: The modified HSAT was found to be accurate and a reliable way to confirm high clinical probability of OSA in this Veteran population. Additionally, modified HSAT was cost effective compared to traditional evaluation methods and increased access for Veterans. Given the negative health impacts of untreated OSA, accurate and timely diagnosis followed by initiation of appropriate treatment methods is of the utmost importance. Future directions discussed. Support (If Any):